NUMERICO-ANALYTICAL INVESTIGATION OF DYNAMIC CONTACT PROCESSES OF CYLINDRICAL MACHINE PARTS - L. P. VOVK; B. V. SOBOL (Advanced Engineering Research)
Mathematical aspects of the solution of spatial contact dynamic problem of contacting the cylindrical details of cars are considered. Updating of the method of the superposition is presented, that allows to conduct analytical research of the intense-deformed condition and to make practical recommendations according to intensity of local concentration of pressure in irregular zones of contact that practically predetermines strength parameters of the contact pair. The mechanical characteristics of interaction of piston fingers of internal combustion engines with the  head of the rod and piston lugs are considered as a numerical experiment.